Ecological System Influences in the Treatment of Pediatric Chronic Pain - Deirdre E Logan; Lisa Engle; Amanda B Feinstein; Christine B Sieberg; Penny Sparling; Lindsey L Cohen; Caitlin Conroy; Dana Driesman; Akihiko Masuda (Pain Research and Management)
Family, school and the peer network each shape the chronic pain experience of the individual child, and each of these contexts also represents a domain of functioning often impaired by chronic pain. The goal of the present article is to summarize what is known about these bidirectional influences between children with pain and the social systems that surround them. Case reports that illustrate these complex, transactional forces and their ultimate impact on the child’s pain-related functioning are included. A case involving siblings participating in an intensive interdisciplinary program for functional restoration and pain rehabilitation highlights how parents change through this treatment approach and how this change is vital to the child’s outcomes. Another case involving a child undergoing intensive interdisciplinary treatment illustrates how school avoidance can be treated in the context of pain rehabilitation, resulting in successful return to the regular school environment. Finally, an acceptance and commitment therapy-focused group intervention for children with sickle cell disease and their parents demonstrates the benefits of peer contact as an element of the therapeutic intervention.